How Will You Contribute? A Look at an Instructional Strategy to Improve Student-Centered Learning - Christine Kenney (Networks: An Online Journal for Teacher Research, 2018)
The dreaded blank stares, looking down at a phone, or the student who falls asleep. University instructors know students who demonstrate these behaviors and have watched them disengage during class. Students might wish to engage, but may not know how. The purpose of this article is to examine the use of contribution strategies with undergraduate students in an effort to foster their engagement in class. Through a semester-long study, students’ usage of seven contribution strategies within course discussions was examined through frequencies and audio recordings. Findings reveal that students incorporated the seven contribution strategies into course discussions however they did so at varying levels. Implications for the research suggest that when given the opportunity to actively contribute students do so; however, the instructor must foster an environment where active contribution is possible and valued.
Keywords: contribution strategies; action research; undergraduate